Evaluasi Nilai Heritabilitas dan Daya Hasil Galur Jagung SMB-5 Hasil Seleksi Massa Varietas Lokal Berte Asal Bali pada Daerah Basah - SANG MADE SARWADANA; A.A. MADE ASTINIGSIH (Fakultas Pertanian Universitas Udayana, 2013)
Evaluation of The Heritability Value and Yield Potential of Corn of SMB-5 Lines As Results of Mass Selection of Berte, A Local Variety Native to Bali on Wet Areas The objective of this research was to find out population homogeneities of SMB-5 line as a result of mass selection of Berte and to find out the agronomic character of the SMB-5 line, mainly the yield potential and the heritability value. This experiment was conducted at Tangguntiti village, Selemadeg Timur District, Tabanan regency which is categorized as wet-type area (B climate type) during six months, started from April until September 2007. This experiment was designed as a Randomized Complete Block Design with nine corn genotypes as treatments. Those corn genotypes were Seraya (Sr), Cicih Tombong (Ct), Arjuna (Ar), Ketan (Kn), Pulut Putih (Pp), Populasi Campuran (Cm), Tongtongan (Tt), SMB-5 (Sm) and Ketokong (Kt). Each treatments was replicated three times, therefore, twenty seven experiment plots were used. There was significant different among corn genotypes used in this research for almost quantitative variables observed. However, there was no significant different occurred in some variables i.e. the number of corn cobs per plant, the weight of 1000 seeds with 12% of water content and the weight of 1000 oven-dry weight seeds. The weight of 1000 seeds with 12% of water content per hectare was 63.17 quintal ha-1 for SMB-5 line and 61.99 quintal ha-1 for Populasi campuran, both were not statistically difference. Almost all variables observed showed high value of heritability.